Creatinina sérica en pacientes con osteoartrosis que reciben tratamiento crónico con antiinflamatorios no esteroideos - Gonzales Sandoval, Karla María (2015)
Title: "Serum creatinine in patients with osteoarthritis who receive chronic treatment Anti-Inflammatory Agents, Non-Steroidal." Objective: Determine serum creatinine values in patients with osteoarthritis who receive chronic treatment with NSAIDs. Methodology: A descriptive study was performed using medical histories of adults older than 18 years treated at the HRDT during 2012-2013 reporting a diagnosis of osteoarthritis and who used NSAIDs for at least three months period and also met the inclusion criteria and exclusion. Nonparametric tests were used to analyze creatinine variable. Results: 203 medical records of patients with diagnosis of osteoarthritis, where it was found that 98% of the population have normal serum creatinine and 2% of the population has altered in such securities, within which presented alteration: males showed a 1% change in creatinine values serum and in females 2% of alteration. The average age of the population was 62.13 years. By applying the Kruskal Wallis worth X2 = 20,248 and a p-value = 0.000 we indicated that sufficient level of 5% (p-value <0.05) evidence to say that differs creatinine time NSAID consumption. He also found that serum creatinine did not differ by sex, age, BMI or location of osteoarthritis. Conclusion: The serum creatinine values in patients with osteoarthritis who receive chronic treatment with NSAIDs, are within normal limits in 98% of the population and 2% of the population has altered values. The serum creatinine in patients with osteoarthritis receiving chronic NSAID treatment differs according to the time of consumption of NSAID